L'usage de la vidéo dans l'enseignement d'une langue seconde : document à interpréter ou exemple à suivre ? - Erard, Yves (My University, 2010)
The aim of this contribution is to show that what the CECR means by oral comprehension activities is not very clear. Using an example of this type of activity in wich a video serves as document, it will point out the problem. Using an example of an other type of activity in wich a video serves as model, it will show how to solve it.
Keywords: Teaching French as a foreign language; CEFR; oral comprehension; video; language activity; ordinary language; Wittgenstein